2019
DOI: 10.1155/2019/8745487
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol Promotes Wnt/β-Catenin Signaling through WIF1 in Ovariectomy-Induced Osteoporosis

Abstract: Osteoporosis is one of the most frequent diseases related with age. Previously, we have reported a novel potential drug, gossypol, for the treatment of osteoporosis through its regulation of Wnt/β-catenin signaling. This study aims to identify the detailed mechanism of gossypol in human osteoporosis. Mice injected with gossypol were subjected for RNA-seq analysis and the transcription level of WIF1 was shown to be decreased dramatically in gossypol-treated mice, which was further confirmed by qRT-PCR and weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Signaling pathways include immune system [109], signal transduction [110], extracellular matrix organization [111], adaptive immune system [112], neutrophil degranulation [113], innate immune system [114], metabolism [115], diseases of metabolism [116] and Hemostasis [117] were responsible for advancement of COPD. MPO (myeloperoxidase) [190], CTSD (cathepsin D) [1389], KLF10 [1390], FRZB (frizzled related protein) [1391], DUSP1 [1392], IL1B [1393], CCL11 [1394], LMNA (lamin A/C) [1395], WIF1 [1396], IL1RN [1397], IFNG (interferon gamma) [1398], CX3CL1 [1399], BMP2 [1400], CDKN1A [1401], BMP4 [1402], ICAM1 [1403], CD34 [1404], IL33 [1405], FASLG (Fas ligand) [1406], KDM6B [1407], TNF (tumor necrosis factor) [1408], GDF15 [1409], IL2 [1410], INPP4B [1411], FABP4 [1412], CYP2C19 [1413], CXCR4 [1414], DKK2 [1415], PLCB4 [1416], ANXA1 [1417], DUSP6 [1418], CORIN (corin, serine peptidase) [1419], F8 [1420], DDIT4 [1421], IL1R2 [1422], S100A4…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include immune system [109], signal transduction [110], extracellular matrix organization [111], adaptive immune system [112], neutrophil degranulation [113], innate immune system [114], metabolism [115], diseases of metabolism [116] and Hemostasis [117] were responsible for advancement of COPD. MPO (myeloperoxidase) [190], CTSD (cathepsin D) [1389], KLF10 [1390], FRZB (frizzled related protein) [1391], DUSP1 [1392], IL1B [1393], CCL11 [1394], LMNA (lamin A/C) [1395], WIF1 [1396], IL1RN [1397], IFNG (interferon gamma) [1398], CX3CL1 [1399], BMP2 [1400], CDKN1A [1401], BMP4 [1402], ICAM1 [1403], CD34 [1404], IL33 [1405], FASLG (Fas ligand) [1406], KDM6B [1407], TNF (tumor necrosis factor) [1408], GDF15 [1409], IL2 [1410], INPP4B [1411], FABP4 [1412], CYP2C19 [1413], CXCR4 [1414], DKK2 [1415], PLCB4 [1416], ANXA1 [1417], DUSP6 [1418], CORIN (corin, serine peptidase) [1419], F8 [1420], DDIT4 [1421], IL1R2 [1422], S100A4…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt inhibitory factor 1 (WIF1) was also identified as a critical factor for gossypol treatment. One study confirmed that gossypol suppresses WIF1 levels via methylation of the WIF1 promoter ( Liang et al, 2019 ). Collectively, these findings confirm that gossypol is another potential drug for OP therapy.…”
Section: Progress In Op Therapy Via Regulation Of Epigenetic Inherita...mentioning
confidence: 94%
“…The most intriguing pathogenic alterations of this gene are related to its methylation pattern. A proposed treatment against osteoporosis, Gossypol, was observed to promote bone proliferation through the methylation and inhibition of the WIF-1 promoter [ 463 ]. On the other hand, WIF-1 methylation has been associated with bone tumors.…”
Section: Inhibitorsmentioning
confidence: 99%